If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -8k + -9k + -4 = 0 Reorder the terms: 1 + -4 + -8k + -9k = 0 Combine like terms: 1 + -4 = -3 -3 + -8k + -9k = 0 Combine like terms: -8k + -9k = -17k -3 + -17k = 0 Solving -3 + -17k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -17k = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -17k = 0 + 3 -17k = 0 + 3 Combine like terms: 0 + 3 = 3 -17k = 3 Divide each side by '-17'. k = -0.1764705882 Simplifying k = -0.1764705882
| 29-4x=4 | | 2y+9fory=-6 | | 6f-7f-1=-5-5f | | 3a+a+25=225 | | 2+2x-5=5x+3 | | x+7+3x-1+2x+5=0 | | 5-y=-2x-5 | | X=32+2x | | 4x*1=0 | | -q=8+q | | 23x^2+50x+25=0 | | 2x+(x+1)=4 | | m^3+4=1 | | 2x+x+1=4 | | 0.2f=-8.4 | | -12(2-t)=14t | | 4v+10+v-9= | | x+6(4)=29 | | (2d-7)=(2+4d)2 | | a+.75a=21 | | 0=2x^2+1x-6 | | 3x+17+3+7x=x | | 2(-6y+29)-4y=-6 | | (2(23)+21)= | | y,5-6=8 | | 3+n^3=6 | | 90+x+(2x+21)=180 | | 5u-37=2(u+1) | | 90+x+(2x+21)= | | 2+y+3=0 | | -1-8b=-8-9b | | -3y+(6*2)=-6 |